Platelet-Associated Matrix Metalloproteinases Regulate Thrombus Formation and Exert Local Collagenolytic Activity. Issue 12 (December 2015) - Mastenbroek, Tom G.; Feijge, Marion A.H.; Kremers, Romy M.W.; van den Bosch, Marion T.J.; Swieringa, Frauke; De Groef, Lies; Moons, Lieve; Bennett, Cavan; Ghevaert, Cedric; Johnson, Jason L.; van der Meijden, Paola E.J.; Cosemans, Judith M.E.M.
Abstract : Objective—: Platelets are increasingly implicated in processes beyond hemostasis and thrombosis, such as vascular remodeling. Members of the matrix metalloproteinase (MMP) family not only remodel the extracellular matrix but also modulate platelet function. Here, we made a systematic comparison of the roles of MMP family members in acute thrombus formation under flow conditions and assessed platelet-dependent collagenolytic activity over time. Approach and Results—: Pharmacological inhibition of MMP-1 or MMP-2 (human) or deficiency in MMP-2 (mouse) suppressed collagen-dependent platelet activation and thrombus formation under flow, whereas MMP-9 inhibition/deficiency stimulated these processes. The absence of MMP-3 was without effect. Interestingly, MMP-14 inhibition led to the formation of larger thrombi, which occurred independently of its capacity to activate MMP-2. Platelet thrombi exerted local collagenolytic activity capable of cleaving immobilized dye-quenched collagen and fibrillar collagen fibers within hours, with loss of the majority of the platelet adhesive properties of collagen as a consequence. This collagenolytic activity was redundantly mediated by platelet-associated MMP-1, MMP-2, MMP-9, and MMP-14 but occurred independently of platelet α-granule release ( Nbeal2 −/− mice). The latter was in line with subcellular localization experiments, which indicated a granular distribution of MMP-1 and MMP-2 in platelets, distinct from α-granules. Whereas MMP-9 protein could not be detected inside platelets, activated platelets did bind plasma-derived MMP-9 to their plasma membrane. Overall, platelet MMP activity was predominantly membrane-associated and influenced by platelet activation status. Conclusions—: Platelet-associated MMP-1, MMP-2, MMP-9, and MMP-14 differentially modulate acute thrombus formation and at later time points limit thrombus formation by exerting collagenolytic activity. Abstract : Supplemental Digital Content is available in the text.